2018
DOI: 10.3892/ol.2018.8960
|View full text |Cite
|
Sign up to set email alerts
|

Effects of connective tissue growth factor on prostate cancer bone metastasis and osteoblast differentiation

Abstract: Previous studies have demonstrated that connective tissue growth factor (CTGF) is expressed at increased levels in prostate cancer bone metastasis mouse models and patients with prostate cancer which metastasizes to the bone; however, the underlying molecular mechanism(s) remain unknown. The present study investigated the function of CTGF in osteoblast differentiation and its effect on prostate cancer bone metastasis by analyzing CTGF gene expression and transcription at different levels of invasion, metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Siu et al demonstrated that KLF4 functions as a transcription factor to activate the AR-miR-1 signaling pathway to constrain the tumor-suppressive role of miR-1 [50]. CTCF, a downstream transcription activator of Smad and Myc signaling, contributes to slowing down metastasis in PCa through directly interacting with the miR-127-3p promoter, in which the downregulation of miR-127-3p accompanies proteasome subunit beta type-5 (PSMB5) elevation and subsequently leads to the activation of BM [55][56][57]. All of the above research draws a large picture of the regulatory mechanism of BM in PCa cells, and Figure 1 summarizes these signaling cascades.…”
Section: Other Minor Emt Contributorsmentioning
confidence: 99%
“…Siu et al demonstrated that KLF4 functions as a transcription factor to activate the AR-miR-1 signaling pathway to constrain the tumor-suppressive role of miR-1 [50]. CTCF, a downstream transcription activator of Smad and Myc signaling, contributes to slowing down metastasis in PCa through directly interacting with the miR-127-3p promoter, in which the downregulation of miR-127-3p accompanies proteasome subunit beta type-5 (PSMB5) elevation and subsequently leads to the activation of BM [55][56][57]. All of the above research draws a large picture of the regulatory mechanism of BM in PCa cells, and Figure 1 summarizes these signaling cascades.…”
Section: Other Minor Emt Contributorsmentioning
confidence: 99%
“…In the early stage of PCa, most patients have no obvious symptoms due to the insidious onset and slow growth of the tumor [ 3 ]. Once PCa is advanced, it can cause symptoms such as abnormal urination, pelvic discomfort, erectile dysfunction, and even bone pain and spinal cord compression, which can greatly affect the quality of life of patients [ 4 , 5 ]. Accordingly, there is an urgent need to develop effective biological approaches to improve diagnosis and prognosis of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…CCN2, as observed in breast cancer, CCN3 and CCN4 levels are up regulated in prostate cancer and bone-metastatic cells or corresponding bone metastasis (Dankner et al 2019 ; Kim et al 2020 ; Ono et al 2013 ). Consistently, exogenous administration of CCN2 prior to in vivo injection increases number and size of bone metastases, whereas its inhibition reduces bone metastasis and related osteosclerosis (Kim et al 2020 ; Zhang et al 2018 ). CCN3 in conditioned medium from prostate cancer cells favours osteoclastogenesis via both RANKL-dependent and RANKL-independent pathways in vitro and forced overexpression of CCN3 in PCa and LnCAP C4-2 cells enhances osteolytic potential and TRAP-staining in metastatic lesions (Chen et al 2013b ).…”
Section: Bone Metastasis Of Other Cancersmentioning
confidence: 87%